Culturable soil microbial biodiversity in post-mining areas of the Konin lignite mine and its potential for ecosystem restoration - Lewandowska, Magdalena; Richert, Agnieszka; Hejda, Natalia (Ecological Questions, 2026)
Post-mining areas represent strongly transformed environments that provide unique conditions for studying microbial diversity and ecological succession. This study aimed to characterize the bacterial and fungal communities isolated from soil samples collected in the post-mining landscapes of the Konin Lignite Mine (central Poland). Cultivable microorganisms were isolated and identified using molecular methods based on 16S rRNA (bacteria) and ITS (fungi) gene sequencing. Taxonomic classification was conducted using BLAST and SILVA (bacteria) and UNITE (fungi) databases. Identified taxa included bacteria from genera Pseudomonas, Bacillus, Micrococcus, and Stutzerimonas, and fungi from genera Cladosporium, Trichoderma, and Penicillium. Many of these microorganisms exhibit traits relevant to bioremediation and supporting plant growth in degraded soils. Our findings highlight the ecological potential of soil microbiota in post-industrial ecosystems and their importance in restoration efforts.